Strategi Promosi Pengembangan Pariwisata Melalui Media Sosial Di Desa Suka Nalu Kecamatan Barusjahe Kabupaten Karo - Maya Anjeli Ginting; Binur Panjaitan; Ade Putra Arif Panjaitan; Diana Situmeang; Tio R J Nadeak (Jurnal Mahasiswa Kreatif, 2023)
If tourism promotion is not accompanied by a good communication strategy, it will affect the existence of the tourist attraction itself. Based on that, the aim of this research is to find out about SRP Ernala's tourism promotion strategy through Instagram (IG) social media. This research uses primary data and secondary data. In this research, the primary data is the results of interviews with managers, employees and visitors to SRP Ernala tourism in Karo Regency, secondary data is social media content from the SRP Ernala tourist village as well as previous research related to this research. This research uses qualitative research methods with descriptive analysis which collects data through observation data, documentation and interviews with 6 informants. From the research results, the SRP Ernala tourism development promotion strategy used by tourism managers is in line with the theory of promotional forms, product, price, place, promotion, promotions used via Instagram social media. SRP Ernala's tourism development promotion strategy through social media is quite effective and has received positive responses from various visitors. In this way, SRP Ernala tourism is developing